Bushido Culture in Novel “47 Ronin” by John Allyn - Wahyu Pratama Putra; Hamzah A. Machmoed; Harlinah Sahib (Hasanuddin University, 2022)
The research aims at finding out the portrait and implementation of the bushido culture in the novel of 47 Ronin. The research type is library research which applied sociological approach and data were analyzed through qualitative method. The research result shows that the influence of the bushido culture is upheld by the samurai. The novel is based on fact of the Japanese people at the period, the influence of religious values is then channeled into public life, and it is still adhered to today in some aspects of their lives.